Makna Literasi Keuangan dalam Keberlangsungan Usaha Industri Rumah Tangga Perempuan Bali - Indrayani, Luh (Universitas Pendidikan Ganesha, 2020)
This study aims to reveal the meaning of financial literacy in the sustainability of a home industry business. The method used is qualitative, with a phenomenological approach through the epoche process. The research results reveal that literacy as financial information and knowledge is the basis for financial management in an effort to improve business so that it can survive and even develop in various market activities. The theoretical implication of financial literacy has a big role in financial management, the use of financial products and services for income distribution in the economic field. Practically, this research can be used as a material consideration for business owners to enrich their knowledge and financial information as a basis for increasing business sustainability in order to have competitiveness so as to contribute to economic development. Financial literacy attainment as the basis for business financial management in realizing business prosperity